Oral trichomoniasis in raptors in Southern Brazil - Echenique,Joanna V.Z. (2019)
ABSTRACT: A retrospective study of oral trichomoniasis cases in raptors was carried out at “Laboratório Regional de Diagnóstico” of “Faculdade de Veterinária” of “Universidade Federal de Pelotas” (LRD-UFPel) from December 2014 to August 2017. Seven necropsy reports were reviewed. All raptors including Falconiformes and Strigiformes orders were from periurban zones. Four birds were adults, and there was no apparent sex predisposition. Clinical signs included dysphagia, regurgitation, and anorexia. Gross lesions were characterized by multifocal yellow to coalescent caseous nodules adhered to the oral cavity, which extended to the entrance of the esophagus. Microscopically, the lesions were characterized by severe focally extensive heterophilic granulomatous stomatitis. Trichomonas gallinae was isolated in modified Diamond medium of all samples collected from birds. It is believed the transmission occurred by the predation of domestic pigeons (Columbia livia domestica) contaminated with T. gallinae that agglomerate in patios of grain processing complexes.